Delayed Total Pneumothorax and Reexpansion Pulmonary Edema Requıred Mechanical Ventilation: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Reexpansion Pulmonary Edema; Pneumothorax; Mechanical Ventilation.